Electric vehicle navigation and cluster dispatch for reliable low-carbon traffic–Power systems - Wang, Shunqi; Xiang, Yue; Chen, Lin; Sun, Zhou; Hu, Shangjian; Guo, Mingyang; Hu, Haifeng; Tong, Jun; Huang, Yifan; Chen, Liang; Liu, Junyong (Frontiers in Energy Research, 2023)
The large-scale integration of electric vehicles (EVs) into the city system for charging will affect the operation of both traffic and distribution networks. An electric vehicle navigation and cluster dispatch model is proposed for improving the overall charging efficiency of EVs on the transportation network and increasing the voltage level of the distribution network. Firstly, a simplified model of vehicles and traffic road network is established, and a cell transmission model (CTM) is used to simulate the real traffic network. The traffic system takes into account charging EVs, discharging EVs and other vehicles, and traffic congestion is considered. Then, a coupled model of the traffic-power system is built for the orderly charging of electric vehicles upon arrival at a charging station. The model considers the coupling of the two systems on the time scale and the charging/discharging power at each charging station node is controlled. The validity of the model is verified in a coupled system of 357 cells traffic network and modified IEEE33 nodes. The results show that it can ensure a good guarantee of the distribution network voltage reliability and reveal the scheduling process of the traffic network. The proposed model also provides a reference for the planning of charging stations in the distribution network.